Psycaria - emotion detector for a p sychiatrist / Ayesha Anees Zaveri ... [et al.] - Zaveri, Ayesha Anees; Nazar, Mobeen; Faisal, Nabiha; Shehmir, Sarama; Parveen, Misbah; Sami, Naveera (Universiti Teknologi MARA, 2022)
Every person will experience stress around the world, some healthy, called EUSTRESS and some unpleasant, named DISTRESS. Good pressure and stress promote success. Stress damages people's lives and health and causes various diseases. On the other hand, psychiatrists have a hard time treating their patients owing to a lack of time. They need innovative and intelligent equipment to treat their patients. We prepared a device that can detect a person's POSITIVE and NEGATIVE emotions through a smartwatch and a gadget that can sense body temperature, respiration, and heart rate. After witnessing these parameters, it can store the results on a website depending on the patient's condition. For example, the psychiatrist observed one patient for at least seven days regarding the days' results stored on a website. After seven days, the report is generated. The goal of psychiatrists in keeping their patients for seven days is to assess their emotional health and determine if they need to adjust their treatment. This system detects eight positive and negative emotions through heartbeat, respiratory, and body temperature sensors. These sensors are incorporated by utilizing machine learning. Web-based apps interpret sensor readings. Psychiatrists will analyze and report the website's results.